Awangardowy Eliot [przełożył Tomasz Cieślak-Sokołowski] - Perloff, Marjorie (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The author of the article describes a mode of twentieth century poetry for which the key concept is that of constructivism — the specific understanding that language is itself a field of meaning-making. In the successive parts of her paper, Marjorie Perloff ponders on Eliot’s The Love Song of J. Alfred Prufrock with special regard to his actual literary practice. The poetic mode of instability and dislocation, the poetics of indeterminacy — she tries to convince us — are to become, in their more extreme forms, the characteristic mode of such contemporary poets as John Ashbery, Robert Creeley, Lyn Hejinian and Charles Bernstein.